Pendidikan Kesehatan Mental untuk Mengembangkan Minat dalam Bidang Olahraga - Muhammad Farid Ilhamuddin; Retno Tri Hariastuti; Titin Indah Pratiwi; Bambang Dibyo Wiyono; Issac Briyan Alisyahbana (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Title of Community Service: Mental Health Education to Develop Interest in Sports in the “Young and Young Work” Community Group, Kedungsari Village, Kemlagi District, Mojokerto Regency. Determining the level of psychological well-being of a youth can be seen through how they express themselves when participating in sports activities organized by the “Muda Mudi Berkarya” community group. This is evidenced by the fact that almost all young people are less enthusiastic when carrying out sports activities organized by the “Muda Mudi Berkarya” community group. Therefore, it is important to look at the relationship between youth interest in sports and psychological well-being. Psychological well-being can increase the interest of young people assisted by the Young Mudi Berkarya community group in the field of sports.